EFEITO DA MODIFICAÇÃO TÉRMICA NA RESISTÊNCIA BIOLÓGICA DA MADEIRA DE EUCALIPTO - Medeiros, Jaqueline Rocha de (2021)
This research aimed to evaluate the effects of heat treatment on the biological resistance of wood from 14-year-old Eucalyptus hybrid clones. Three Eucalyptus grandis x Eucalyptus urophylla clones (A, C and E) and three trees from each of them were used. From these, samples of central planks were taken from the second log (4.20 m) of the trees and transformed into boards with dimensions of 2.5 x 10 x 60 cm (thickness x width x length), which were subjected to thermal treatment (185 and 200ºC). Samples were then taken for chemical analyses and biological resistance tests. Chemical analyses were performed in triplicate for each chemical constituent (total extractives, total lignin, holocellulose, and ash) for clone and temperature. The assays with dry wood termites (Crypototermes brevis), no choice feeding and choice feeding test, during 45 days; and with subterranean or arboreal termites (Nasutitermes corniger), no choice feeding and choice feeding tests, during 28 or 45 days (respectively). Mass loss, wood wear, number of holes (dry wood), and termite mortality (no choice feeding) were evaluated. The fungus assay during 12 weeks and brown rot fungi (Gloeophyllum trabeum and Rhodonia placenta) and white rot fungi (Irpex lacteus) were tested. Heat treatment altered the proportion of chemical components in the wood, causing a reduction in biological resistance to the xylophagous organisms tested. For the choice feeding tests with dry and subterranean wood termites the samples thermo-modified at 185 ºC were more consumed. Among the fungi used, those that caused the most severe attacks were the ones that caused brown rot and also altered the color of the wood more intensely.